Exogenous ketone bodies and the ketogenic diet as a treatment option for neurodevelopmental disorders - Omori, Naomi Elyse; Malys, Mantas Kazimieras; Woo, Geoffrey; Mansor, Latt (Frontiers in Nutrition, 2024)
Background: Despite being the most prevalent neurodevelopmental disorders, there are comparatively few treatment options available to patients presenting with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). The ketogenic diet has historically shown therapeutic utility in treating refractory epilepsy, an adjacent neuropsychiatric condition, in children, adolescents and adults. The following review explores preclinical and clinical literature focusing on the therapeutic potential of the ketogenic diet and exogenous ketone body supplementation in treating common neurodevelopmental disorders.Method: A narrative review of extant literature was conducted across the domains of perinatal nutrition, ASD, and ADHD. Preclinical and clinical studies focusing on the effect of either the ketogenic diet or exogenous ketone supplementation as a treatment option were included for review.Results: 14 preclinical and 10 clinical studies were included for discussion. Data supporting the use of a ketogenic intervention for neurodevelopmental disorders is mixed. High heterogeneity in study design was noted for preclinical models, ketogenic intervention, and outcomes measured.Studies evaluating ketogenic interventions for neurodevelopmental disorders remain in their infancy in terms of both the depth and scope of available literature. The safety and tolerability of ketogenic diets and supplements means there would be value in exploring their effectiveness further in clinical studies.